Mentorship strategies in teacher education - Dikilitaş, Kenan 1973-; Mede, Enisa 1970-; Atay, Derin 1964- (Advances in educational marketing, administration, and leadership (AEMAL) book series, 2018)
"This book creates a central source for researchers, teacher educators and practitioner mentors. It addresses a number of aspects of mentoring such as mentoring strategies, mentored learning, mentee development through mentors, learning to mentor and learning mentoring. It covers a number of issues such as mentor and mentee experiences, learning, impact and development perspectives"...